PENGARUH PERUBAHAN DALAM PEMBINAAN HUKUM SIYASAH SYAR‘IYYAH - Abdul Rahman, Mohamad Zaidi (Jurnal Syariah, 2008)
This article outlines the influences of socio-political changes towards development of Siasah Syar‘iyyah approach. This approach is parallel with the maxim of fiqh ‘changes of ahkam (rules) are permissible with the change in times’. However, ‘the change of ahkam’ should be treated by appropriate methodology to gain the understanding of maslahah from Islamic perspective.